THE EFFECT OF VARIOUS TYPES BIOPESTICIDES ON THRIPS POPULATION DEVELOPMENT IN CHRYSANTEMUM PLANTS (Dendrathema grandiflora Tzvelev) - Karel F. LALA; Max TULUNG; Jantje PELEALU; Eva M. MAMAHIT; Budi MARWOTO (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Chrysanthemum (Dendrathema grandiflora Tzvelev) is an Asteraceae family, very popular ornamental plant in the family, generally characterized by aromatic, deeply lobed, alternate leaves and often large and showy flowers. The main problems in chrysanthemum business is Thrips sp. This pest can attack chrysanthemum plants in all plant growth stadia, but the most harmful attacks occur in early formation phase. Thrips pest control recommendations on chrysanthemums have been provided by various authorized agencies, including through the use of resistant varieties. This study aimed to determine the effectiveness of various bio-pesticides and microbial pesticides. The study was conducted using a randomized block design with 5 replications. The experimental unit consists of 1 m2 land-plot, and each plot is planted with 100 stool with 10 x 10 cm space. Results indicated that the Neem seed, Annona muricata, and Tinospora crispa extract as biopesticides, effectively controlled the total population of Thrips nympa and adult, but has no significant different on the extracts level between three plant species on Thrips population density. The microbial pesticide (Beuveria sp.,) Jatropha curca leaf extract, Mentha cordifolia leaves, were less effective in controlling the Thrips population, although it was better than the Thrips population in control.